Assessment of finite volume modeling approaches for intermediate temperature Solid Oxide Fuel Cells working with CO-rich syngas fuels. (16th November 2015) - Spallina, V.; Mastropasqua, L.; Iora, P.; Romano, M.C.; Campanari, S.
Abstract: The application of Solid Oxide Fuel Cells (SOFCs) to a wide variety of syngas fuels, as those generated from coal or biomass gasification, may represent an important opportunity for the improvement of electric efficiency and for emission reduction in the electric sector. The paper presents an assessment of the impact on SOFC performance prediction of the effect of the combined electrochemical oxidation of CO and H2, proposing additional analyses to delve into the effects of different SMR and WGS kinetics models, along with the risk of carbon deposition. The work is based on a finite-volume model for SOFC simulation, updated to examine two different electrochemical reaction approaches where (i) the first considers only the electrochemical conversion of H2 and neglects the possibility of a direct CO oxidation at electrode surface; (ii) the second calculates the current contribution of both H2 and CO oxidation. The two models are compared against different test cases with low and high-CO syngas, representative of different primary fuels, discussing the relative proportion of H2 and CO-related current densities depending on the inlet fuel composition. A sensitivity analysis is carried out on the electrochemical model, focusing on the activation overpotentials. We show that the resulting enhanced H2 –CO electrochemical model allows a better understanding of the fuel composition and H2 /CO ratios effect on the cell performances. Highlights: Modelling of Intermediate temperature SOFCs. Assessment of different model approaches with hydrogen and hydrogen + CO oxidation. Assessment of different kinetic model for reforming and water gas shift reactions. Setup of a finite volume model for planar IT-SOFC operating with high CO fuels and sensitivity analysis. Assessment of carbon deposition.